2011
DOI: 10.2135/cropsci2010.01.0037
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Susceptible Allele Inverting the Dominance of Rust Resistance in Soybean

Abstract: Soybean rust (SBR) is the most threatening fungal disease in the major soybean [Glycine max (L.) Merr.] production areas around the world. In spite of the availability of chemical control with fungicides, the increase of production costs as well as operational difficulties associated with fungicide use for disease management has prompted the search for resistant genes in the soybean germplasm. Five genes (Rpp1, Rpp2, Rpp3, Rpp4, and Rpp5) have been reported as capable of conferring SBR resistance in soybean. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…The presence of mixed reactions was also reported in genetic populations derived from PI 200456 and PI 224270 [48]. In addition, inversion of dominance by a susceptibility allele has been reported in populations derived from the cross of some PIs crossed with different susceptible parents [49]. In our field evaluations in Ha Noi, the mapping population was inoculated with locally collected unpurified inoculum.…”
Section: Discussionsupporting
confidence: 61%
“…The presence of mixed reactions was also reported in genetic populations derived from PI 200456 and PI 224270 [48]. In addition, inversion of dominance by a susceptibility allele has been reported in populations derived from the cross of some PIs crossed with different susceptible parents [49]. In our field evaluations in Ha Noi, the mapping population was inoculated with locally collected unpurified inoculum.…”
Section: Discussionsupporting
confidence: 61%
“…Garcia et al (2011) reported the alteration of gene action type in Rpp1 locus pointing out the relative status of Rpp resistant genes. Differences in genetic behavior of rust resistance genes have been (Table 3) but further detailed analysis goes beyond the scope of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Past researches on host resistance to soybean rust have identified six major resistance loci (Rpp: resistance to P. pachyrhizi), named Rpp1 to Rpp6 and an allele (Chakraborty et al 2009, Garcia et al 2008, Hartwig 1986, Hartwig & Bromfield 1983, Li et al 2012, McLean & Byth 1980, Ray et al 2009). These Rpp genes confer specific resistance to a limited set of P. pachyrhizi isolates, some of which have been used to develop Rpp gene-carrying cultivars (Garcia et al 2011, Hartman et al 2011 and Rpp-pyramided lines (Lemos et al 2011, Maphosa et al 2012, Yamanaka et al 2015b) using conventional strategies.…”
Section: Introductionmentioning
confidence: 99%